State of the eye health system in the Pacific: is medical technology available and used by mid-level eye care workers? - Benoit Tousignant; Matthew Pearce; Julie Brûlé Biu Sikivou; Graeme Nicholls (James Cook University, 2020)
Introduction: The aim of this study is to describe the availability, use and comfort with ophthalmic equipment and medications by mid-level eye care workers in Papua New Guinea and Pacific Island countries and territories as indicators of the state of eye care in the Pacific. Methods: Health information system data, from a workforce support program to Pacific mid-level eye care workers, were analysed for availability and comfort with use of ophthalmic equipment and topical medications. Results: For refraction equipment, access was excellent (98% for retinoscopes and trial lenses) 'very frequent use' range was 42-74% and 'high comfort of use' range was 54-86%. Equipment for ocular health assessment is widely available (slit lamps 67%), with high comfort levels (78-100% 'very comfortable'). Over 70% of respondents have access to topical diagnostic medications, 98% have access to at least one type of antibiotic drops and 63% have access to at least one topical corticosteroid. Conclusion: Overall, trained mid-level eye care workers in the Pacific seem well equipped for ocular health and refractive assessments. Comfort levels are encouraging, but also highlight areas for continuing professional development. Access to ophthalmic medications appears acceptable in the region for low morbidity anterior segment conditions.